2008
DOI: 10.1158/1055-9965.epi-07-0284
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of p16INK4A and p14ARF Genes in Prognosis of Oral Carcinoma

Abstract: Background: Oral cancer patients are found to have poor clinical outcome and high disease recurrence rate, in spite of an aggressive treatment regimen. The inactivation of INK4A/ARF loci is reported to be second to p53 inactivation in human cancers. The purpose of this study was to assess the prognostic significance of the molecular aberrations in the INK4A locus for effective identification of aggressive oral carcinoma cases needing alternate therapy. Materials and Methods: The study composed of 116 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 24 publications
6
47
0
1
Order By: Relevance
“…In the present study, we have examined the GO tissue samples that were identified to be carrying wild type p53 and H-ras genes in earlier study (Jayaraman et al, 2012), for the occurrence of mutations in the oncogene PIK3CA and tumor suppressors p14ARF, p16INK4a and p21 Waf1/Cip1 . Exons 9 and 20 of PIK3CA subunit of PI3K protein, exons 1α, 1β and 2 of p14ARF and p16INK4a and exon 2 of p21 Waf1/Cip1 were investigated as mutations in these regions were found to be highly prevalent in OSCCs (Murugan et al, 2008;Sailasree et al, 2008;Abbas et al, 2009). The finding that none of the analyzed GO samples carried mutation in the above four genes suggests non-neoplastic nature of this condition, which is in agreement with our earlier report.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we have examined the GO tissue samples that were identified to be carrying wild type p53 and H-ras genes in earlier study (Jayaraman et al, 2012), for the occurrence of mutations in the oncogene PIK3CA and tumor suppressors p14ARF, p16INK4a and p21 Waf1/Cip1 . Exons 9 and 20 of PIK3CA subunit of PI3K protein, exons 1α, 1β and 2 of p14ARF and p16INK4a and exon 2 of p21 Waf1/Cip1 were investigated as mutations in these regions were found to be highly prevalent in OSCCs (Murugan et al, 2008;Sailasree et al, 2008;Abbas et al, 2009). The finding that none of the analyzed GO samples carried mutation in the above four genes suggests non-neoplastic nature of this condition, which is in agreement with our earlier report.…”
Section: Discussionsupporting
confidence: 90%
“…Hence loss of function mutations in either one of them, p14ARF or p16INK4a is likely to promote carcinogenesis. Indeed deletions and mutations in both p14ARF and p16INK4a have been observed in several cancers including OSCCs (Kresty et al, 2002;Sailasree et al, 2008). p21 Waf1/Cip1 is an universal inhibitor of cyclin dependent kinases and is under transcriptional control of wild type p53.…”
Section: Introductionmentioning
confidence: 99%
“…28 There is a wide range in the reported frequencies of strong and diffuse p16 INK4a overexpression in oral cavity squamous cell carcinoma. [29][30][31][32][33][34][35][36][37][38] Here, in studying a large cohort of patients with oral cavity squamous cell carcinoma, we confirm that p16 INK4a overexpression is uncommon (15.5%). Furthermore, we demonstrate that p16 INK4a overexpression has a protective effect with respect to disease progression (hazard ratio 0.11, 95% CI 0.02-0.63).…”
Section: Discussionsupporting
confidence: 65%
“…We consider this conclusion to be drawn cautiously, as some publications summarized various RT modalities as primary RT, RCT and adjuvant RT after radical surgery in one and the same group. 15,24,34,35,38,39 A conclusion regarding radiosensitivity should be based on results of tumors treated with primary RT or RCT only, which are directed against the tumor volume as a whole. Primary RT normally differs from adjuvant RT in decreased dosage and single fractionation directed against possible microscopic tumor cell remains, utilized after primary radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on prognosis of HPV induced p16 positive OPSCC including tumor collectives treated by different treatment modalities such as surgery, 26,37 RT, 37 RCT 25,40 or OPSCC treated by various, but summarized modalities. 15,20,21,24,34,35,38,39 In addition, our single-institutional study requires validation in large prospective trials prior to implementation of p16 as a potential prognostic marker in OPSCC.…”
Section: Discussionmentioning
confidence: 99%